The Use of Animation Videos to Improve Students’ Speaking Skill - Cut Irmayunda; Sofyan A. Gani; Nira Erdiana (Research in English and Education Journal, 2020)
The objective of this study is to figure out whether the use of animation videos improve students’ speaking skill to the second-year students at SMP Negeri 16 Banda Aceh. The method of this study was quantitative research (experimental study) with one group pre-test and post-test design. The sample of this research was one class at VIII-1 which consists of 30 students. The researcher used simple random sampling to determine the sample. The researcher used an oral test to collect the data about giving a dialogue (an expression to invite someone) with their partner. In analyzing the data, the researcher used a statistical formula to measure the data. The calculation result showed that the mean score of students' pre-test score was 21 and the mean score of the post-test was 41. Then, the t-score was 4.89 and the t-table was 2.045. It can be seen that the t-score was higher than the t-table. In conclusion, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. As a result, the use of animation videos in learning English improves students speaking skills.